(untitled) (Jagannath University Journal of Life and Earth Sciences, 2025)
ChalanBeel, one of the major inland depressions of marshy character, is in the vulnerable condition due to various human interventions. The number of population of the ChalanBeel area has increased manifold in the recent years. To accommodate the increasing population, huge Beel areas were drained out and reclaimed by the locals. Roads, highways, embankments, bridges, culverts and other infrastructures were developed in this area. Due to increase of agricultural practices, the number of wetlands reduced over the period of time. Overfishing, pollution, unplanned infrastructures, lack of institutional coordination, lack of public awareness, etc. have become responsible for environmental degradation in this area. The present paper assesses the human intervention induced land use land cover changes in the ChalanBeel area. This study was conducted based on both primary and secondary data. Primary data was collected from field survey through interviewing the locals and the secondary data was collected from various published and online sources as well as satellite images were used to identify the land use land cover changes. The study reveals that built-up areas increased from 40.87 sq. km to 144.06 sq. km. and water bodies declined from 258.65 sq. km. to 90.63 sq. km in between 2003 and 2023, and the low-lying areas remained nearly same in that period. Land use land cover changes have significant impacts on the local people’s lives and livelihoods. It is important to reduce the human intervention induced land use land cover changes to ensure the planned growth of the surveyed areas. Jagannath University Journal of Life and Earth Sciences, 10(1) 40-58